Pengintegrasian Wahana Permainan Wisata Alam Ngarai Sianok dan Wisata Buatan MiFan Water Park Padang ke dalam Materi Fisika - Rifai, Hamdi; Yohandri, Yohandri; Sari, Dewi Puspa; Emafri, Wenda (JURNAL EKSAKTA PENDIDIKAN (JEP), 2019)
Edupark is a park with a variety of rides and ecosystems that can be used as a learning tool. Ngarai Sianok, Bukittinggi is a national Geopark area that has a nature tourism vehicle and Minang Fantasy (MiFan) Padang Panjang Water Park is an artificial tourist game vehicle. In general, visitors to attractions only take advantage of the natural landscape or a vehicle to take photos, sports such as jogging, hiking, camping, family gathering or low impact outbound. Without them knowing it, there are many physics concepts in both natural and artificial games that can be used as learning resources by integrating into high school physics learning in the form of physics teaching materials or integrated in learning models. However, there are actually educa-tional values, especially the physical concepts contained in the game. The purpose of this study is to integrate Edupark Ngarai Sianok and MiFan Water Park because it remembers so many Physics concepts found in natural or artificial tourism. The process of collecting data through observation and study of literature. The results showed that Edupark physics could be integrated in learning physics according to the 2013 curriculum